Deliberate self-harm and associated risk factors in young adults: the importance of education attainment and sick leave - Lunde, Ketil Berge; Mehlum, Lars; Melle, Ingrid; Qin, Ping (Social Psychiatry and Psychiatric Epidemiology, 2021)
Purpose The prevalence of deliberate self-harm (DSH) is high in young adults. However, few studies have examined risk in this specific age group. We, therefore, examined the relative influence and interactive nature of a wide range of potential sociodemographic and sick leave related risk factors in young adults, aged 18–35 years, using Norwegian register data. Methods All subjects with at least one episode of hospital presentation for DSH registered in the Norwegian Patient Register during the period 2008–2013 were compared with age, gender and date matched population controls using a nested case–control design. The relative influence of factors and their interactions were assessed using conditional logistic regression and recursive partitioning models. Results 9 873 study cases were compared to 186 092 controls. Socioeconomic status, marital status, sick leave and several demographic factors influenced risk for DSH. Specifically, low education (OR 7.44, 95% CI 6.82–8.12), current sick leave due to psychiatric disorders (OR 18.25, 95% CI 14.97–22.25) and being previously married (OR 3.83, 95% CI 3.37–4.36) showed the highest effect sizes. Importantly, there was an interaction between education and sick leave, where those with either low education and no sick leave (OR 13.33, 95% CI 11.66–15.23) or high education and sick leave (OR 18. 87, 95% CI 17.41–24.21) were the subgroups at highest risk. Conclusion DSH in young adults is associated with multiple sociodemographic and health disadvantages. Importantly, the two high-risk subgroups imply different pathways of risk and a need for differentiated preventative efforts.